ANALISIS PENERAPAN SISTEM INFORMASI MANAJEMEN KORESPONDSI DALAM MENINGKATKAN PENDAPATAN DAERAH PADA BADAN PENDAPATAN DAERAH KABUPATEN BANDUNG BARAT - Sophia Rahmi; Said Bambang Nurcahya (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2022)
Local Government Revenue is one of the instruments of the regional government that comes from tax collections on the economic potential in its working area. In carrying out activities, the Regional Government requires other Regional Revenues derived from regional original income or from transfers between regions and transfers from the center. The West Bandung Regency Government has economic potential from the services, finance, trade, mining, industry, agriculture, plantation and agricultural sectors. fisheries so that income from this tax sector must be worked out efficiently and accurately so that the community in this case taxpayers find it easy to get tax services so that in the long term the increase in income increases, the impact of the Covid 19 pandemic on the economy in West Bandung Regency is felt, the service sector tourism is one of the most affected so that the Regional Revenue Agency of West Bandung Regency made a breakthrough to implement correspondence using a correspondence management information system to increase regional income. The application analysis used in this study uses a SWOT analysis with a descriptive methodology by displaying comparative statistics on revenue realization in 2020 and 2021. In the application of this application, of course, there are still many obstacles that must be corrected related to digital tax correspondence.